2017
DOI: 10.33736/ijbs.3155.2017
|View full text |Cite
|
Sign up to set email alerts
|

The Impact Of ASEAN Free Trade Area On Intra-Asean Manufacturing Trade

Abstract: This study investigates the effects of ASEAN Free Trade Area (AFTA) agreement on the bilateral manufacturing trade between the 10 member countries of ASEAN and 39 of their trading partners. The period ofstudy covers 1995 to 2014. Results obtained from panel data analysis of the gravity model with random effectsshow that the economic sizes, populations, relative endowments, common language and geographical factors like distance, island, landlocked and neighbour are significant determinants of the bilateral manu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…The distance variable is a proxy of transportation costs, it's indicated that if the distance further, then rubber export between Indonesian and trade partner countries will decrease significantly. These findings are in line and support the study results by Wong et al (2017). On the other side, contrary to the study results by Akhmadi (2017).…”
Section: Empirical Results Of Indonesian and Thailand Rubber Exportsupporting
confidence: 86%
See 2 more Smart Citations
“…The distance variable is a proxy of transportation costs, it's indicated that if the distance further, then rubber export between Indonesian and trade partner countries will decrease significantly. These findings are in line and support the study results by Wong et al (2017). On the other side, contrary to the study results by Akhmadi (2017).…”
Section: Empirical Results Of Indonesian and Thailand Rubber Exportsupporting
confidence: 86%
“…In early April 2015 the number of this type of agreement has increased by 19.8 percent or become 612 RTAs, and 406 of which are running. At present time every country on the planet at least has two RTAs (Wong et al, 2017). Globalization and trade liberalization, with the increase of trade agreement activities amongst some countries, have presented disagreement and contradiction opinions amongst economists (Bradford & Chilton, 2019;Rodrik, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sejalan dengan prinsip yang dikemukakan oleh World Trade Organization (WTO) dalam rangka mendorong pembentukan kerjasama ekonomi di setiap negara melalui skema perdagangan bebas guna meningkatkan perpindahan arus barang dan modal, maka saat ini banyak negara yang telah membangun dan menyepakati kebijakan tersebut tidak hanya secara bilateral tapi juga multilateral (Rohendi, 2014). Demikian halnya dengan ASEAN sebagai federasi beberapa negara yang terletak di Kawasan Asia Tenggara yang juga telah membangun kerjasama perdagangan bebas secara internal di antara seluruh negara anggota yakni Indonesia, Kamboja, Myanmar, Laos, Brunei Darussalam, Malaysia, Filipina, Singapura, Thailand, dan Vietnam dalam bentuk kebijakan ASEAN Free Trade Area (Wong et al, 2017). Di mana saat ini juga anggota ASEAN telah bertambah satu negara dan total menjadi sebelas negara anggota yakni Timor Leste yang pasti juga akan melakukan penyesuaian terhadap kebijakan perdagangan bebas tersebut.…”
Section: Pendahuluanunclassified
“…Their results suggest that tariff elimination under the Common Effective Preferential Tariff Scheme facilitates production and sales networks for AFTA's original member countries, including Indonesia. Wong, Liew, and Arip (2017) examine the effects of AFTA on bilateral manufacturing trade between 10 ASEAN countries and their trading partners. Their results suggest that AFTA has generated trade creation effects in exports, while its trade creation effects in imports outweigh its import diversion effects.…”
Section: Economic Effects Of Afta In Indonesiamentioning
confidence: 99%